An assessment of the effectiveness of the delivery of services and benefits of the GSIS Iloilo field operations department applying the premium-based policy - Salazar, Felipe Jr. F.
This study ws conducted to assess the effectiveness of the GSIS Iloilo Filed Operations Department in the delivery of services and benefits to its members. Specifically, the sstudy aimed to identify specific group of members who are most receptive to the program and policies of the system, describe the members' level of awareness of the System's programs and policies, determine the effectiveness of the System in the delivery of its services and benefits in terms of members' awareness of the System's programs and benefits, accuracy and accessibility of its database, extensiveness of its information dissemination, timeliness and promptness and members' satisfaction and recommend new programs and policies for the improvement of the System's delivery of services and benefits. The descriptive method of research was employed in this study. The study was conducted at the GSIS Iloilo Field Operating Department. A total of 48,000 members served as respondents of the study. The sample respondents were drawn using random sampling. The data were gathered using the survey questionnaire developed by the researchers, duly validated by selected jurors. The construction of the questionnaire was based on the specific objectives of the study. Questions were formulated in such a way that all variables of the study were adequately measured. The data gathered through the survey questionnaires were coded and encoded for computer programming and processed/analyzed using the statistical software. Statistical pacjages for the social Sciences (SPSS). The frequency distribution, percentages and the measures of central tendency such as mean, median and mode were used to describe the different variables of the study. The sample respondents in this study were found to be in their thirties, predominantly female, married, college graduates holding permanent employment status. Most of them are from Iloilo City specifically from the National Government Agencies and Government Owned and Controlled corporations. They have been members of the System for 1-10 years. In terms of awareness of the System's programs and policies, most of the respondents are moderately aware of it except for one program which is the Tulong sa Local n Pamahalaan Program. Most respondents perceive the GSIS database as moderately accurate and accessible. Liason officers are main sources of information about the System's policies and programs. They find the System's information dissemination drive effective. Furthermore, most of the respondent's application for benefit claims and loan packages were approved within the time allotted for processing. Taking into account the accuracy and accessibility of database, extensiveness of information dissemination, timeliness and promptness and members' satisfaction, most of the respondents gave GSIS a "good" rating in rendering services and benefits.